Enigmatic exosomal connection in lung cancer drug resistance - Sambit K. Patra; Rajeev K. Sahoo; Stuti Biswal; Shikshya S. Panda; Bijesh Kumar Biswal (Elsevier, 2024)
Lung cancer remains a significant global health concern with limited treatment options and poor prognosis, particularly in advanced stages. Small extracellular vesicles such as exosomes, secreted by cancer cells, play a pivotal role in mediating drug resistance in lung cancer. Exosomes have been found to facilitate intercellular communication by transferring various biomolecules between cancer cells and their microenvironment. Additionally, exosomes can transport signaling molecules promoting cancer cell survival and proliferation conferring resistance to chemotherapy. Moreover, exosomes can modulate the tumor microenvironment by inducing phenotypic changes hindering drug response. Understanding the role of exosomes in mediating drug resistance in lung cancer is crucial for developing novel therapeutic strategies and biomarkers to overcome treatment limitations. In this review, we summarize the current knowledge on conventional and emerging drug resistance mechanisms and the involvement of exosomes as well as exosome-mediated factors mediating drug resistance in lung cancer.